2009
DOI: 10.3944/aott.2009.042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ankle position on intracompartmental pressures of the leg

Abstract: Dorsiflexion of the ankle increases ICP significantly in both anterior and deep posterior compartments. The results of this study may have clinical implications for the conservative management of both CECS and tibial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…In the early 2000s, field observations also indicated that free-technique evolutions led to enhanced ankle dorsiflexion. Tsintzas et al [31] have reported in patients with CECS a significant increase in pressure of the anterior compartment of the lower leg during ankle dorsiflexion. In runners, where the prevalence of CECS is increased, several studies demonstrated that changing the running style in athletes with CECS could prevent the occurrence of symptoms [32][33][34][35].…”
Section: Ski Technique Likely Influences the Cecs Prevalencementioning
confidence: 97%
“…In the early 2000s, field observations also indicated that free-technique evolutions led to enhanced ankle dorsiflexion. Tsintzas et al [31] have reported in patients with CECS a significant increase in pressure of the anterior compartment of the lower leg during ankle dorsiflexion. In runners, where the prevalence of CECS is increased, several studies demonstrated that changing the running style in athletes with CECS could prevent the occurrence of symptoms [32][33][34][35].…”
Section: Ski Technique Likely Influences the Cecs Prevalencementioning
confidence: 97%
“…This leads to a marked increase in the eccentric activity of the anterior structures of the lower leg, in particular the tibialis anterior muscle. 32 The running technique concept that was used in the studies by Diebal et al 12 , 13 focused on a forefoot strike pattern (ie, landing on the ball of foot) by applying shorter strides and a significantly increased step rate (180 steps per minute or more). These adaptations reduce ground reaction impact forces by minimizing ground contact time and vertical displacement, but, more important, they shift the eccentric loading of the anterior compartment musculature of the leg to the posterior lower leg structures such as the Achilles tendon and the gastrocnemius-soleus muscle complex.…”
mentioning
confidence: 99%
“… 7 Local arteriolar pressure has been shown to decrease by 0.78 mmHg for every cm of ankle elevation above the right atrium. 8 …”
Section: Discussionmentioning
confidence: 99%